KLASIFIKASI CITRA SATELIT SENSOR MODIS DENGAN PRINCIPAL COMPONENT ANALYSIS - Zebua, Charles B (Jurnal Ilmu Komputer dan Sistem Informasi, 2013)
This report discuses the methods used to classificatian. This method begins whit classification process using the Principal Component Analysis (PCA). Thera are twenty two pieces to the input image. Twenty two image is a multispectral image size of 500x500 pixels with the maximum taken .tiff format using MODIS satellite, and has a grayscale color space